Pengaruh Tekanan Ketaatan, Locus of Control, Kompleksitas Tugas dan Self Efficacy Terhadap Audit Judgement (Studi pada Kantor Akuntan Publik di Surakarta dan Semarang) - Safitri, Dyah Ayu, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2017)
Auditor is a professional whose job carrying out an audit of the entity's financial statements and draw conclusions. Audit judgment a significant influence on final conclusion, so that will affect the opinion will be issued by the auditor. Research objective to determine the effect of obedience pressure, locus of control, task complexity, and self efficacy on audit judgement. The sample in this study is the auditors who worked in KAP firm in Surakarta and Semarang. The method used is survey method with questionnaire data collection techniques as much as 47 respondents. Mechanical analysis using classical assumption test and multiple regression analysis. The results showed that the obedience pressure, locus of control, and self efficacy effect on audit judgement, while the task complexity no effect on audit judgement.